Selective harmonic elimination methods for a cascaded H-bridge converter - Watson, Alan James (2009)
In recent years there has been an increased demand for integration of renewable energy into the electricity grid. This has increased research into power converter solutions required to integrate renewable technology into the electricity supply. One such converter is a Cascaded H-Bridge (CHB) Multilevel Converter.